INDONESIAN-ENGLISH CODE-MIXING BY “KUY-ENTERTAINMENT” YOUTUBE CHANNEL - Monica Monica Heraldine; Bella Natasia Panjaitan; Joana Febiola; Nurma Dhona Handayani (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2022)
Code-mixing is the use of two or more languages by inserting one language element into another language element in one sentence. This research used descriptive qualitative research to aimed the types and reasons for code-mixing that were realized in the “Kuy-Entertainment” YouTube video. The method of collecting data from this qualitative research is observational. And the technique of analyzing data is descriptive. This research used theory from Muysken (2000) to analyzed about the types of code-mixing, and for the reason used theory from (Hoffman, 1991). The researchers found 15 data of types and reasons of code-mixing. Those were 3 types in the utterances, 12 data of insertion, 2 data of alternation, and 1 data of congruent lexicalization. And for the reason, the researchers found 4 reasons of code-mixing, those were 9 data of talking about a particular topic, 2 data of quoting somebody else, 3 data of being emphatic about something, and 1 data of intention of clarifying the speech content for the interlocutor.